2018
DOI: 10.3892/ol.2018.8538
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter cross‑sectional screening of the BRCA gene for Chinese high hereditary risk breast cancer populations

Abstract: Abstract. Due to lack of systematic reviews, BRCA, DNA Repair Associated (BRCA) mutations in the Chinese population are not completely understood. The following study investigates the prevalence and type of BRCA mutations in Chinese patients with high hereditary risk of breast cancer (BC).Patients Drwere recruited from 14 cities between October 2015 and February 2016, and were selected based on family and personal medical history. BRCA mutations were analyzed by collecting blood samples from all participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…In this study, we found that patients with triple‐negative breast cancer had a higher BRCA1 mutation rate than those with non‐triple‐negative breast cancer. Our results agree with those of previous studies in Chinese patients with breast cancer (Li et al, ; Liang et al, ; Wei et al, ). We did not find significant associations between BRCA1/2 mutation status and age; family history of breast cancer, ovarian cancer, pancreatic cancer, and prostate cancer; number of primary lesions; tumor size; or lymph node metastasis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, we found that patients with triple‐negative breast cancer had a higher BRCA1 mutation rate than those with non‐triple‐negative breast cancer. Our results agree with those of previous studies in Chinese patients with breast cancer (Li et al, ; Liang et al, ; Wei et al, ). We did not find significant associations between BRCA1/2 mutation status and age; family history of breast cancer, ovarian cancer, pancreatic cancer, and prostate cancer; number of primary lesions; tumor size; or lymph node metastasis.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, 11 BRCA1 mutations were detected in Chinese patients with breast cancer. Four of these mutations (c.1934delC, c.2138C>G, c.2572C>T, and c.3916_3917delTT) have been reported in Chinese populations (Li et al, ; Liang et al, ; Wei et al, ). Five BRCA1 variants have not been reported in the BIC and/or ClinVar databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that BBC is one of the related clinical factors that increases the probability of BRCA mutations [9,20] and remains one of the criteria for recommendation of genetic testing [21]. BRCA mutation rate was about 24% among Chinese women with BBC [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that BBC is one of the related clinical factors that increases the probability of BRCA mutations [9,20] and remains one of the criteria for recommendation of genetic testing [21]. BRCA mutation rate was about 24% among Chinese women with BBC [20]. Interval breast cancers among BRCA mutation carriers have worse clinicopathologic features than screen-detected tumors, and require more aggressive medical and surgical therapy [6].…”
Section: Discussionmentioning
confidence: 99%